Short History of Kosovo’s Indipendence - Sherifi, Isak (Richtmann Publishing, 2012)
Kosovo on its path towards freedom and independence has passed a difficult and bloody history. One of the recent andserious problems that Kosovo was suffering was the Balkan crisis, otherwise known as crisis of former Yugoslavia after the fall of theBerlin Wall. In the geopolitics of the time and historiography Kosovo exploded as a hot point where multiple regional interests whereinterrelated but also wider in the European Union. For the fate of Kosovo many organizations, countries and important personalities wereinvolved. An important point concerns the advantages and disadvantages of the parties in Rambouillet conference on the role of holdingthis conference benefits and losses that the parties had in this conference and the benefits that brought Kosovo in building itsinstitutions.